Experiencia colonial, memoria y olvido en el Paraguay - Ramón Fogel (Caravelle)
This work presents an alternative look in relation to the accounts of hegemonic thought about socio-historical processes; It focuses on the wild Guaraní Indians, who suffered and still suffer today relations of domination legitimated by prejudice. In the formulations are found contrasting experiences of these infidels living in the Jesuit reductions, and who were renowned as faithful Indians. The analysis shows how ethnocultural collectivities that resisted colonial domination and neocolonial experiences have been ignored or vilified in the imposed truths set by the powerful. This work covers a long term and exploits Spanish colonial administration’s documentation, from religious sources and post-independence historical records. To these sources I added the oral memory testimonies that I collected more than 30 years ago, which have not yet been exploited. These coinciding testimonies can certainly counteract memory’s force which dominant groups seek to impose.